Brain inspired optoelectronic integrated receiver chip for wireless optical communication - Xie, Sheng; Zhao , Yuhao; Wang, Lihua; Cong , Jia; Mao , Xurui (Frontiers in Physics, 2022)
Inspired by the mechanism of visual attentional selection, a wireless optical communication (WOC) Integrated receiver consisting of a vertical double junction photodetector (VDJ-PD) and an attentional selection circuit (ASC) is presented. The whole receiver is fabricated in standard CMOS technology. The VDJ-PD can realize optical signal detection and wavelength identification. The ASC activates the competition among the two PN junctions in VDJ-PD to select the signal with significant feature in real-time while discarding non-significant signals. A higher-order signal modulation scheme is applied by the proposed receiver to obtain a high transfer rate, and all data are decoded using color features. The optical testing results show that parallel and real-time communication of the red and blue light can be achieved, and the rise time is 4.47 μs. To measure the anti‐interference performance of the receiver, a water tank is used to simulate a harsh communication environment. Results indicate that the real-time and reliable communication requirements in a harsh channel condition are satisfied. When the SNR is 0.75dB, an accurate information decoding can still be achieved. Moreover, the whole processing procedure does not require the participation of ADC, CPU and memory, consequently avoiding the von Neumann bottleneck.